2022
DOI: 10.1111/jgh.16087
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of ASK1 involvement in liver diseases and related potential therapeutic targets: A critical pathway molecule worth investigating

Abstract: Since the discovery of apoptosis signal‐regulated kinase 1 (ASK1), the signal transduction mechanism and pathophysiological process involved in its regulation have been continuously revealed. Many previous studies have identified that ASK1 is involved and plays a critical role in the development of diseases affecting the nervous, cardiac, renal, and other systems. As a mitogen‐activated protein kinase (MAPK) kinase kinase, ASK1 mediates apoptosis, necrosis, inflammation, and other pathological processes by act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 78 publications
(148 reference statements)
0
4
0
Order By: Relevance
“…ASK1, functioning as a MAPK kinase kinase, has been reported to phosphorylate JNK, thereby regulating cell apoptosis and various cellular physiological and pathological functions . This underscores the key role of ASK1 in NASH, and inhibiting the ASK1 pathway along with its downstream JNK signaling pathway emerges as a promising strategy to inhibit NASH. , In previous studies, the ASK1 signaling pathway has been demonstrated to activate in different in vivo and in vitro NASH models accompanied by a significantly increase in ASK1 phosphorylation . TRAFs, including TRAF2 and TRAF6, have been shown to interact with ASK1 and activate under different stimuli. , We have identified for the first time that lycopene can inhibit the phosphorylation of ASK1 in both in vivo and in vitro models.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…ASK1, functioning as a MAPK kinase kinase, has been reported to phosphorylate JNK, thereby regulating cell apoptosis and various cellular physiological and pathological functions . This underscores the key role of ASK1 in NASH, and inhibiting the ASK1 pathway along with its downstream JNK signaling pathway emerges as a promising strategy to inhibit NASH. , In previous studies, the ASK1 signaling pathway has been demonstrated to activate in different in vivo and in vitro NASH models accompanied by a significantly increase in ASK1 phosphorylation . TRAFs, including TRAF2 and TRAF6, have been shown to interact with ASK1 and activate under different stimuli. , We have identified for the first time that lycopene can inhibit the phosphorylation of ASK1 in both in vivo and in vitro models.…”
Section: Discussionmentioning
confidence: 95%
“…54 This underscores the key role of ASK1 in NASH, and inhibiting the ASK1 pathway along with its downstream JNK signaling pathway emerges as a promising strategy to inhibit NASH. 16,55 In previous studies, the ASK1 signaling pathway has been demonstrated to activate in different in vivo and in vitro NASH models accompanied by a significantly increase in ASK1 phosphorylation. 55 TRAFs, including TRAF2 and TRAF6, have been shown to interact with ASK1 and activate under different stimuli.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following activation, ASK1 phosphorylates and activates downstream targets, particularly the mitogen-activated protein kinase (MAPK) kinase kinase family members like MKK4 and MKK7. These, in turn, stimulate the c-Jun N-terminal kinase (JNK)/p38 signaling pathways, ultimately triggering the activation of transcription factors responsible for regulating genes associated with stress responses, cell proliferation, and apoptosis [ 9 ]. Posttranslational modifications regulate the kinase activity of ASK1.…”
Section: Introductionmentioning
confidence: 99%